Modelowanie wpływu potencjału rozwoju zrównoważonego na stopę życia w regionie - Korol, Janusz; Szczuciński, Przemysław (Modelling of the impact of sustainable development potential on the standard of living in the R=region, 2006)
The aim of the paper is to define the key determinants of the standard of living understood in terms of 1) job opportunities and 2) providing basic social needs. The theoretical construction of the research model is based on the assumption that the standard of living in a region is significantly affected by its economic, social and natural potential and resources, as well as their proper use. The following methods were employed in the analysis of the relationships in question: structural equation modelling, soft modelling and taxonomic methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 353-362